Silicone rubber with mussel-inspired adhesive coatings for enhancing antifouling property and blood compatibility - Cho, Youngjin; Seo, Si Yoong; Park, Bang Ju; Joung, Yoon Ki; Han, Dong Keun (한국고분자학회, 2017)
Silicone rubber is widely used in various biomedical fields. However, the silicone surface is known to cause biofouling and thrombosis issues due to its higher hydrophobic property. In this study, to improve its antifouling property and blood compatibility, silicone rubber was modified by coating of hyaluronic acid (HA) or poly(ethylene glycol) (PEG). To enhance adhesive property of HA and PEG on the silicone surface, HA and PEG were modified by introducing the amino groups of dopamine (DA) to the carboxyl group of each polymer. The modified HA (HA-DA) and PEG (PEG-DA) were confirmed by 1H nuclear magnetic resonance (NMR) and the coated surfaces were characterized with contact angle, X-ray photoelectron spectroscopy (XPS), and micro-bicinchoninic acid (micro-BCA) analyses. To compare antifouling property and blood compatibility, adsorbed proteins, adhered platelets, and anticoagulation on the modified surfaces were evaluated by fluorescence microscopy, scanning electron microscopy, and activated partial thromboplastin time (APTT) assay, respectively. The property of cell adhesion on the modified surface was evaluated by NIH 3T3 fibroblast as a model cell system. Protein, platelet, and fibroblast showed low adsorption and adhesion on the modified silicone rubber surfaces compared to the unmodified one. Especially, the third coated silicone rubber surfaces were found to strongly resist protein adsorption as well as platelet and fibroblast adhesion. These results indicated that the antifouling property and blood compatibility were enhanced significantly on HA-DA and PEG-DA immobilized silicone rubbers. Therefore, these modified silicone rubbers can be used in various biomedical applications.